Evidence-based interventional pain medicine : according to clinical diagnoses - Zundert, Jan van (Wiley-Blackwell, 2012)
Unrelieved chronic pain is a worldwide epidemicChronic pain has been subject to multiple international initiatives through the World Health Organization. Interventional Pain Medicine, use of minimally invasive techniques to relieve pain, is the best approach when simpler measures such as physical therapy or medications fail. However, these procedures can be associated with significant risk and expense. Establishing uniformity in diagnostic criteria and procedural performance can reduce both morbidity and unnecessary procedures, and hence healthcare expenditures. While other texts explain how to.